COMPARATIVE ANALYSIS OF SUPRAPATELLAR AND INFRAPATELLAR APPROACHES IN INTRAMEDULLARY NAILING OF TIBIAL SHAFT FRACTURES: A RETROSPECTIVE COHORT STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Intramedullary nailing is the standard treatment for tibial shaft fractures. The infrapatellar approach has been widely used; however, it is associated with technical difficulties and a high incidence of anterior knee pain. The suprapatellar approach has emerged as an alternative, offering potential advantages in fracture alignment and functional recovery. Methods: This retrospective comparative cohort study included 60 patients with tibial shaft fractures treated with interlocking intramedullary nailing. Patients were divided into two groups based on the surgical approach: suprapatellar (n=30) and infrapatellar (n=30). Functional and radiological outcomes were assessed over a follow-up period of six months using range of motion (ROM), Lysholm knee score, radiological union, operative parameters, and complication rates. Results: Radiological union was achieved in the majority of patients in both groups, with no statistically significant difference. The suprapatellar group demonstrated significantly better functional outcomes, with higher ROM and Lysholm scores at six months (p